2018
DOI: 10.1111/tmi.13160
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of sarcocystosis in the local communities of Pangkor and Tioman Islands using recombinant surface antigens 3 (rSAG3) of Sarcocystis falcatula

Abstract: Objective To investigate the seroprevalence of Sarcocystosis in the local communities of Pangkor and Tioman islands, Malaysia, by using antigenic recombinant surface antigens 2 and 3 from Sarcocystis falcatula (rSfSAG2 and rSfSAG3) as the target proteins via Western blot and ELISA assays. Methods SfSAG2 and SfSAG3 genes were isolated from S. falcatula and expressed in Escherichia coli expression system. A total of 348 serum samples [volunteers from both islands (n = 100), non‐Sarcocystis parasitic infections p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This is a continuation study from our previous work on rSf-SAG3, where rSfSAG3 showed immunodominant characteristic and a suitable protein candidate for the development of serodiagnostic tools. The experimental design and the type of tested sera were the same as our previous work [17]. We were unable to test sensitivity and specificity of rSfSAG4 due to absence of true positive serum (patient infected with S. nesbitti) in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a continuation study from our previous work on rSf-SAG3, where rSfSAG3 showed immunodominant characteristic and a suitable protein candidate for the development of serodiagnostic tools. The experimental design and the type of tested sera were the same as our previous work [17]. We were unable to test sensitivity and specificity of rSfSAG4 due to absence of true positive serum (patient infected with S. nesbitti) in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Co-infection of Sarcocystis and Toxoplama was reported in Malaysia although no report on the co-infection between Sarcocystis and Plasmodium [9,21]. Similar to rSfSAG3 evaluation [17], rSfSAG4 was tested with anti-T. gondii and anti-Plasmodium via Western blot to eliminate potential cross-reactivity. Additionally, sequence of rSfSAG4 was subjected to BLAST analysis to check for the potential similarity with the antigens for other parasites resulted in no significant similarity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation